KEPUASAN MAHASISWA TERHADAP MUTU LAYANAN PENDIDIKAN UNIVERSITAS BINA SARANA INFORMATIKA - Merdekawati, Agustiena; Azlina, Yunidyawati; Wulansari, Murwani (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2024)
The purpose of this study was to determine how much influence student satisfaction has on the quality of education services, to determine the student satisfaction index on the quality of education services, and to find out which services still have to be improved, paid attention to and maintained. The population in this study are students of Bina Sarana Informatika University and sampling using probability sampling with simple random sampling method. physical evidence, reliability, and assurance variables have a positive and significant effect on the quality of education services. While partially the variables of empathy and responsiveness do not have a positive and significant effect on the quality of educational services. Based on the results of the CSI score, it produces a score of 78%, meaning that students are satisfied with the service. Results with the IPA method, there are still several statements that must be improved. These results cannot be separated from the role of lecturers, administrative staff and sections, facilities and others who are in the Bina Sarana Informatika University environment.